NILAI-NILAI PENDIDIKAN ISLAM DALAM FILM NEGERI 5 MENARA - usman, fakhriyah (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2024)
: Negeri 5 Menara is the work of Ahmad Fuadi, which was originally a novel which was later made into a film. This film raises themes such as education, friendship, diversity and life values. The aim of this research is to analyze the values of Islamic education in the film Negeri 5 Menara. The method used in this research is library research or literature review, by analyzing the film Negeri 5 Menara (2012), and collecting data or literature such as books, journals and reading sources related to the film. Based on the analysis of the film Negeri 5 Menara that has been carried out, there are several values of Islamic education that are conveyed to the audience. First, the value of moral education which presents obedience to parents, good manners, honesty, generosity, diligence and trustworthiness. Second, the value of religious education in an Islamic boarding school environment which is full of simplicity and sincerity is a characteristic that must be instilled. Third, the value of motivational education with the Manjada Wajada mantra as a medium to increase enthusiasm for learning and achieve goals. Fourth, the social educational value of the friendship between the main characters of the film Negeri 5 Menara, even though they have different origins, even different goals, does not separate them from remaining friends.